Effect of Perceived Behavioral Factors on Investors’ Investment Decisions in Stocks: Evidence from Nepal Stock Market - Karmacharya, Bibek; Chapagain, Ramkrishna; Dhungana, Bharat Ram; Singh, Kanhaiya (Journal of Business and Management Research, 2022)
This study explores whether the perceived behavioral factors impelling specific investors’ decision-making to contribute to the Nepal Stock Exchange (NEPSE) performance. Applying structural model analysis of the data, it shows that among the four behavioral variables, market, heuristic, and herding factors have significant effects on investment performance. This study observes more reliance and dependence of investors on market information and sentiments. Research findings suggest that investors consider the fundamentals of the stock and consider the investors’ behavior to get a return from the market. The study has been confined to five metropolitan cities with 350 samples randomly obtained in 2018 from different broking firms.